Analyzing The Impact Of Analysts' Forecast Accuracy On Stock Returns: A Meta- Analytic Approach (Journal of Namibian Studies : History Politics Culture, 2024)
Analysts' perspectives on economic risk are a crucial element in the investor decision-making process. Several researchers have immersed themselves in analyst forecasts and stock prices. However, it is imperative to examine the consistency of findings from previous studies in order to draw general conclusions. This analysis is necessary to establish whether analysts' forecasts actually influence stock market returns. Consistency between studies was assessed using a meta-analysis approach, facilitated by Comprehensive Meta-Analysis (CMA) software. Meta-analysis provides an effect size estimate to assess the relationship between the independent variable (analysts' forecasts) and the dependent variable (stock market returns). The results of the heterogeneity test indicate an I-squared value in excess of 50%, signifying substantial variation. Similarly, the correlation analysis reveals a p-value of 0.004, suggesting heterogeneity in the studies of analyst forecasts and stock market returns. Heterogeneity refers to disparities in data within or between studies, attributable to varying research locations and economic conditions. Consequently, the results of this study are heterogeneous due to significant sampling error arising from various research locations and economic circumstances. Thus, it is demonstrated that analysts' forecasts have an impact on stock market returns.